Validation of the photoelectric optogait system to measure racewalking biomechanical parameters on a treadmill - Alvarez, D.; Sebastian, A.; Pellitero, L.; Ferrer-Roca, V. (ISBS Proceedings Archive (Michigan), 2017)
The purpose of this pilot study was to validate the Optogait system to measure racewalking biomechanic parameters on a treadmill. Contact time, flight time, cadence and step length are some of the biomechanic parameters which influence the performance in racewalking. Five subjects were analyzed while racewalking at different speeds on a treadmill. The Optogait system was compared with a high speed video used as reference system. Flight time was overestimated by Optogait when compared with the reference system (0.025 ± 0.014 vs 0.023 ± 0.014 seconds, t = -2.43, p <0,05). No differences were found in contact time or step length. Thus, the present study validates the Optogait system to measure racewalking biomechanical parameters on a treadmill